Comparison of Spatiotemporal Gait Parameters Following Operative Treatment of Trimalleolar Ankle Fractures vs Healthy Controls - Tyler, Andrew F.; Rose, Thomas; Day, Scott; Kenia, Jessica; Horan, Annamarie D.; Mehta, Samir; Donegan, Derek J. (Foot & ankle orthopaedics, 2020)
Background: Controversy continues regarding appropriate indications for posterior malleolus fracture fixation in unstable rotational trimalleolar ankle injuries, with limited data comparing gait in operatively treated trimalleolar ankle fractures vs control populations. The purpose of this study was to evaluate the effect of trimalleolar ankle fracture fixation on gait parameters in the early postoperative period as compared to a healthy control population. Methods: Adult patients having undergone operative treatment of isolated trimalleolar ankle fractures were eligible for inclusion. A total of 10 patients met the inclusion criteria and participated in the analysis. Patients were evaluated using standard parameters of human gait 6 months after their index procedures, with gait values compared to a population of 17 non–age-matched healthy control subjects in addition to literature values of healthy populations of younger and older subjects. Results: Significant differences were noted between the spatiotemporal gait parameters of healthy control subjects and patients who had undergone operative treatment of trimalleolar ankle fractures. However, within the fracture group itself, no differences were found between patients with or without posterior malleolar fixation for any of the tested gait parameters. When patients were compared to literature values of younger and older healthy control populations, they were found to have gait patterns more similar to older rather than younger individuals. Conclusion: Operative fixation of trimalleolar ankle fracture does not restore normal gait function in the early postoperative period. Fixation of the posterior malleolus in particular also does not appear to improve gait characteristics. Patients who undergo surgery for these injuries demonstrate gait patterns similar to those of healthy older adults. Level of Evidence: Level II, Therapeutic (prospective cohort study).